Banks as value-added taxpayers: A case of the Republic of Serbia - Vržina Stefan (Bankarstvo)
Prior research on the taxation of the banking sector were primarily interested in corporate income tax. The issue of taxation of banks with value-added tax (VAT) is relatively neglected. Therefore, this paper examines the VAT status of commercial banks in the Republic of Serbia and the impact of tax regulation changes on their VAT status. In this regard, the research showed that all active banks in the Republic of Serbia are VAT payers: thirteen banks are monthly, while seven are quarterly VAT payers. Although most bank activities are VAT-exempt, some activities such as rental of deposit safe boxes, custody and management of securities, collection of receivables for third parties or consulting services are taxable with VAT at a general rate. Further, a large share of banks changed their status from monthly to quarterly VAT payers after changes in tax regulation regarding the calculation of total turnover for purposes of registration for VAT at the beginning of 2013. In this regard, research results add to the prior research on taxation of banks with VAT, but may also be a useful basis for reforming the system of bank taxation in the future.